Perkembangan Confucius Institute di Amerika Serikat - Fikri Fendi Ferdiansyah (Jurnal Hubungan Internasional, 2019)
Confucius Institute is an educational learning Chinese languageinstitution, integrated within the China Ministry of Education whichhave the task to internationalizing Chinese education in many states. TheConfucius Institute itself has grown rapidly in the United States in thepast ten years. Regarding this phenomenon, there are many anomalieswhich make Confucius Institute should not become bloomed in there, suchas the Chinese-Americans or Chinese spoken are minorities in the UnitedStates. This paper tried to explain why the Confucius Institute can easilyoutspread in the United States during this past ten years. This researchfocused on two things: (1) the relationship between the institution,home country, and host country through bargaining model concept and(2) the application of adaptation strategy with the marketing mix. Theauthor found that the success of Confucius Institute in the United States isbecause there’s a mutually close relationship between the home country andhost country based on bilateral agreement; the mutual close relationshipbetween institution and host country based on bargaining power; and theapplication of marketing mix based on 4P’s and 4C’s.